Powder properties of binary mixtures of chloroquine phosphate with lactose and dicalcium phosphate - Michael Ayodele Odeniyi; Collins Chidi Onyenaka; Oludele Adelanwa Itiola (Universidade de São Paulo, 2010)
A study was conducted on the packing and cohesive properties of chloroquine phosphate in binary mixtures with lactose and dicalcium phosphate powders. The maximum volume reduction due to packing as expressed by the Kawakita constant, a, and the angle of internal flow, θ, were the assessment parameters. The individual powders were characterized for their particle size and shape using an optical microscope. Binary mixtures of various proportions of chloroquine phosphate with lactose and dicalcium phosphate powders were prepared. The bulk and tapped densities, angles of repose and internal flow, as well as compressibility index of the materials were determined using appropriate parameters. The calculated and determined values of maximum volume reduction for the binary mixtures were found to differ significantly (P< 0.05), with the Kawakita plot being more reliable in determining the packing properties. Diluent type was found to influence the flow properties of the mixtures, with dicalcium phosphate giving predictable results while mixtures containing lactose were anomalous with respect to flow. The characterization of the packing and cohesive properties of the binary mixtures of chloroquine with lactose and dicalcium phosphate would be useful in the production of powders, tablets, capsules and other drug delivery systems containing these powders with desirable and predictable flow properties. Realizou-se estudo das propriedades de empacotamento e de coesão do fosfato de cloroquina em misturas binárias com lactose e fosfato dicálcico em pó. O volume máximo de redução devido ao empacotamento, segundo expresso pela constante de Kawakita, a, e o ângulo de fluxo interno, θ, foram os parâmetros de avaliação. Os pós individuais foram caracterizados por seu tamanho e forma de partículas, utilizando microscópio óptico. Prepararam-se misturas binárias de várias proporções de fosfato de cloroquine e lactose e fosfato dicálcico em pó. As densidades de bulk and tapped, os ângulos de repouso e de fluxo interno e o índice de compressibilidade dos materiais foram determinados utilizando-se parâmetros apropriados. Os valores calculados e determinados do volume máximo de redução para as misturas binárias mostraram-se significativamente diferentes (P< 0,05), sendo o traçado de Kawakita mais confiável na determinação das propriedades de empacotamento. O tipo de diluente influenciou as propriedades de fluxo das misturas com fosfato dicálcico, dando resultados previsíveis, enquanto as misturas contendo lactose mostraram-se anômalas com relação ao fluxo. A caracterização das propriedades de empacotamento e de coesão das misturas binárias de cloroquina com lactose e fosfato dicálcico seria útil na produção de pós, comprimidos, cápsulas e outros sistemas de liberação de fármacos contendo esses pós com propriedade de fluxo desejada e previsível.